Comparison of disinfectants effectiveness against staphylococcus aureus and pseudomonas aeruginosa isolated from UiTM Kuala Pilah, Negeri Sembilan Lavatories / Nur Hafiza Shahzan - Shahzan, Nur Hafiza (2017)
The effectiveness of the four brands of disinfectants was compared by conducting phenol coefficient tests at different concentration against two types of organisms. The test organisms are Staphylococcus aureus and Pseudomonas aeruginosa which were isolated from UiTM Kuala Pilah, Negeri Sembilan lavatories. Further gram staining and biochemical tests were conducted to determine the morphological and biochemical characteristics of the selected bacteria isolated from the lavatories. The phenol coefficient value for disinfectant which is greater than 1 indicates that the disinfectant is more effective against Staphylococcus aureus and Pseudomonas aeruginosa compared to that phenol. The results showed that disinfectant A has the highest phenol coefficient value (9) against Staphylococcus aureus, followed with disinfectant B (5.25), C (5.25) and D (1.25) meanwhile disinfectant A and B had the highest phenol coefficient value (9) followed by disinfectant C (1.25) and D (1.25) against Pseudomonas aeruginosa.